Analisis Sistem Ekonomi Konvensional dalam Mendorong Pertumbuhan Ekonomi Nasional - Febi Savira; Norma Hanum Harahap; Reni Ria Armayani Hasibuan (Kajian Ekonomi dan Akuntansi Terapan, 2026)
This study aims to analyze the role of the conventional economic system in driving national economic growth and identify the challenges arising from its implementation. The research method used is a qualitative method with a descriptive approach through library research. Data were obtained from various secondary sources such as books, scientific journals, official government reports, and publications from relevant institutions. Data analysis techniques were carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the conventional economic system plays a significant role in driving national economic growth through market mechanisms, increased investment, and the development of business activities. This system is capable of increasing productivity, economic efficiency, and creating jobs. However, the implementation of the conventional economic system also presents various challenges, such as income disparity, social inequality, the dominance of capital owners, and unequal distribution of social welfare. Therefore, although the conventional economic system is effective in driving economic growth, government intervention is still needed to create equitable development and more inclusive social welfare.